Morpho-molecular diversity and phylogeny of Bysmatrum (Dinophyceae) from the South China Sea and France. Issue 3 (3rd July 2018) - Luo, Zhaohe; Lim, Zhen Fei; Mertens, Kenneth Neil; Gurdebeke, Pieter; Bogus, Kara; Carbonell-Moore, M. Consuelo; Vrielinck, Henk; Leaw, Chui Pin; Lim, Po Teen; Chomérat, Nicolas; Li, Xintian; Gu, Haifeng
ABSTRACT: The dinoflagellate genus Bysmatrum encompasses five epibenthic or tide-pool species and has been characterized by separated anterior intercalary plates. In the present study, we obtained six strains of Bysmatrum from the South China Sea and French Atlantic coast by isolating single cells/cysts from plankton and sediment samples. All strains were examined with light microscopy and scanning electron microscopy. Based on morphological observations, three strains were identified as Bysmatrum subsalsum, characterized by the elongated and rectangular first and a hexagonal second anterior intercalary plate. They differ from each other in the number of sulcal lists and the configuration of the first anterior intercalary plate. One strain was identified as Bysmatrum gregarium and the other two as Bysmatrum granulosum . The cyst-theca relationship of B. subsalsum from the French Atlantic was established by incubation of the cyst, and the geochemical composition of the cyst wall was measured through micro-Fourier transform infrared spectroscopy. Bysmatrum subsalsum from Malaysia shows a bright red stigma in the sulcal area under light microscopy, which was confirmed with transmission electron microscopy: it was identified as a type B eyespot. Small subunit ribosomal DNA (SSU rDNA), partial large subunit ribosomal DNA (LSU rDNA) and internal transcribed spacer (ITS) sequences were obtained from all six strains. The maximum likelihood and Bayesian inference analysis based on concatenated SSU, ITS and LSU sequences revealed that Bysmatrum is monophyletic and nested within Peridiniales. Our strains of B. subsalsum form a new ribotype in the molecular phylogeny (designated as ribotype B). The genetic distance based on ITS sequences among Bysmatrum species ranged from 0.34 to 0.47 and those genetic distances at the intraspecific level of B. subsalsum could reach 0.41, supporting the possibility of hidden crypticity within B. subsalsum .